2021
DOI: 10.1055/a-1728-2249
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Clinical Effects of a Proanthocyanidin-enriched Extract from Rumex acetosa in Periodontally Healthy Carriers of Porphyromonas gingivalis: a Randomized Controlled Pilot Study

Abstract: Rumex acetosa significantly inhibits the adhesion of Porphyromonas gingivalis (P.g.) to eukaryotic host cells in vitro. The objective of this randomized placebo-controlled pilot-trial was to analyze effects of a mouth rinse containing 0.8 % (w/w) of a quantified proanthocyanidin-enriched extract from Rumex acetosa (RA1) on microbiological, clinical, and cytological parameters in systemically healthy individuals without history of periodontitis, harboring P.g. intraorally. 35 subjects received a supragingival d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…There were no severe side effects. The results indicate that the plant extract mouth rinse is safe but does not seem to inhibit colonization of Porphyromonas gingivalis or improve periodontal health following supragingival debridement [117]. Adsorption, distribution, metabolism, and excretion are among the most important parameters, along with pharmacological activity, during drug development preclinical and clinical trials and the standardisation process of a substance.…”
Section: Antidiabetic Activity Of the Plant's Extract Rumexmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no severe side effects. The results indicate that the plant extract mouth rinse is safe but does not seem to inhibit colonization of Porphyromonas gingivalis or improve periodontal health following supragingival debridement [117]. Adsorption, distribution, metabolism, and excretion are among the most important parameters, along with pharmacological activity, during drug development preclinical and clinical trials and the standardisation process of a substance.…”
Section: Antidiabetic Activity Of the Plant's Extract Rumexmentioning
confidence: 99%
“…to eukaryotic host cells in vitro. The randomized placebo-controlled pilot-trial established that mouth wash by 0.8% of proanthocyanidin-enriched extract from the plant effect microbiological, clinical, and cytological parameters [117]. Supragingival debridement was followed by mouth washing (3 times per day) with the extract or placebo (control) for 7 days as adjunct to routine oral hygiene.…”
Section: Antidiabetic Activity Of the Plant's Extract Rumexmentioning
confidence: 99%
“…Kuntze (Plumbaginaceae), popularly known as "baicuru" or "guaicuru" is a plant rich in polyphenols in its rhizomes, especially compounds such as flavan-3-ols and oligomeric proanthocyanidins, with the samarangenins being typical tannin-like polyphenols [15]. These compounds have been described to be strong gingipain inhibitors [15][16][17]. In addition, extracts from L. brasiliense have shown antiseptic activity in genitourinary infections [18] and a variety of studies indicated bacteriostatic, antioxidant, antiviral, and anti-inflammatory potential [15,19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Prevention strategies in livestock and food production are essential to reduce the infection risk, but also specific inhibition of the manifold virulence factors of Campylobacte r has been recognized as a promising tool. Especially, inhibitors of the bacterial adhesion to host cells, the so-called entry blockers or antiadhesive compounds, can help to reduce the early host–pathogen interaction (Sarshar et al 2017 ; Schmuch et al 2015 ; Selbach et al 2023 ; Gottesmann et al 2020a ; Thöle et al 2015 ; Deipenbrock et al 2023 ). Thus, an antiadhesive strategy might also be interesting for reducing the Campylobacter load in livestock.…”
Section: Introductionmentioning
confidence: 99%